2017
DOI: 10.1007/jhep03(2017)105
|View full text |Cite
|
Sign up to set email alerts
|

Hot scalar radiation around a cosmic string setting bounds on the coupling parameter ξ

Abstract: In this work, by investigating the low temperature behaviour of a scalar field around a cosmic string, and assuming stable thermodynamic equilibrium, it is shown that the coupling parameter of the field with curvature must be restricted to a certain range of values whose bounds are determined by the deficit angle of the associated conical geometry.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…[3] for a current application). Just to mention few other examples, local thermal behavior of a massive scalar field near a reflecting wall leads to the existence of bounds on the coupling curvature parameter [4,5], and in the context of semiclassical gravity we report a sort of quantum dragging effect [6] in a spacetime of a cosmic string presenting a dislocation along its axial axis.…”
Section: Introductionmentioning
confidence: 76%
“…[3] for a current application). Just to mention few other examples, local thermal behavior of a massive scalar field near a reflecting wall leads to the existence of bounds on the coupling curvature parameter [4,5], and in the context of semiclassical gravity we report a sort of quantum dragging effect [6] in a spacetime of a cosmic string presenting a dislocation along its axial axis.…”
Section: Introductionmentioning
confidence: 76%
“…We may also quote the more severe effect of spontaneous scalarization, where the vacuum fluctuations lead to phase transitions in certain spacetimes [2]. In the context of a quantum scalar field near a reflecting wall in locally flat spacetime, requirement of thermodynamic equilibrium leads to a restriction on the possible values of the curvature coupling parameter ξ [3,4]. Particularly, it is shown that for higher dimensions the minimal coupling is ruled out.…”
Section: Introductionmentioning
confidence: 99%